(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
Mídia, publicidade e desafios do contemporâneo (ECA‑USP, 2024) is edited by Eneus Trindade, Maria Cristina Dias Alves, and Clotilde Perez. The work aims to consolidate advertising studies in Brazil from a native epistemological perspective, bringing together research on the sector’s transformations. The critical analysis, while acknowledging the book as a milestone in the field, notes that its analytical potential would be enhanced by an explicit theoretical framework crossing the investigations, which would confer greater epistemological cohesion.